Alternating high-intensity interval training and continuous training is efficacious in improving cardiometabolic health in obese middle-aged men - Eric Tsz-Chun Poon; Parco Ming-Fai Siu; Waris Wongpipit; Martin Gibala; Stephen Heung-Sang Wong (Elsevier, 2022)
Background/Objectives: High-intensity interval training (HIIT) or moderate-intensity continuous training (MICT) alone has been shown to improve metabolic health, but the effects of alternating the two training approaches as often practiced in real life remained unclear. The purpose of the current study was to examine the effects of HIIT or MICT alone or alternating HIIT-MICT on cardiometabolic responses in inactive obese middle-aged men. Methods: Forty-two participants (age: 42 ± 5 y; BMI: 26.3 ± 2.1 kg m−2) were randomly assigned to four groups: HIIT (12 x 1-min running bouts at 80-90% HRmax interspersed with 1-min active recovery at 50% HRmax), MICT (40-min brisk walk at 65-70% HRmax), alternating HIIT-MICT or a non-exercise control group (CON). Exercise sessions were conducted three times per week for 16 weeks. Maximal oxygen uptake (VO2max), body composition (by bioelectrical impedance analysis), blood pressure, fasting blood glucose, insulin resistance (HOMA-IR) and lipid profile were assessed at baseline and after the 16-week intervention. Enjoyment and self-efficacy were also assessed at the end of intervention. Results: All exercise groups showed a similar VO2max increase of ∼15% (HIIT: 34.3 ± 4.4 vs 39.1 ± 5.4; MICT: 34.9 ± 5.0 vs 39.4 ± 7.2; and alternating HIIT-MICT: 34.4 ± 5.0 vs 40.3 ± 4.6 mL kg−1min−1) compared to baseline and CON (all p < 0.05). Weight, BMI, % fat and waist circumference also showed similar reductions in all exercise groups compared to baseline and CON (all p < 0.05). No significant group difference was observed for all blood markers. Compared to baseline, total cholesterol decreased after HIIT-MICT, while HIIT significantly decreased fasting insulin level and improved insulin resistance (p < 0.05). Enjoyment, self-efficacy and adherence were similar among all exercise groups. Conclusion: HIIT or MICT alone or alternating HIIT-MICT similarly improve cardiovascular fitness and body composition in obese middle-aged men despite differences in total training volume and time commitment.